Feeding Made With Different Protein Content On Growth And Survival Rate (Chana striata) Fingerlings - Supandi, Teguh Imam; Tang, Usman M; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Study was conducted in January-February 2015, at mandiangin Freshwater Aquaculture Centres,kalimantan selatan province. This study aims to determine the growth of the seed gabus fish (Chana striata)and survival rate of the seed gabus fish(Chana striata) as well as to determine the efficiency of feed consumed of the seed gabus ffish (Chana striata), which are given artificial feed with different protein content. The research method used an experimental with 3 treatments and 3 replications of feeding 2 times a day with different protein content is 30 % , 35 % and 40 %. Test materials used 180 gabus fish (Chana striata) a container of 9 aquarium with stocking density 1 head / liter. The results showed that the artificial feeding with a protein content of 40% better compared to the feeding with a protein content of 30% and 35 %,that is a higher growth of weight gain (2,896 g), daily growth rate (9,03%), survival rate (80%)and feed efficiency 89.65 %.Keyword :Gabus fiish (Chana striata), Fedding made with diferen protein content, and growth.